[OP.2D.03] PULSATILE STRETCH ALTERS EXPRESSION AND PROCESSING OF AMYLOID PRECURSOR PROTEIN IN HUMAN CEREBRAL ENDOTHELIAL CELLS. (September 2016) - Gangoda, S.V.S.; Butlin, M.; Gupta, V.; Chung, R.; Avolio, A.
Abstract : Objective: Amyloid β (Aβ) deposition is a hallmark of Alzheimer's disease (AD). Aβ is generated via enzymatic cleavage of amyloid precursor protein (APP). Increased APP expression is associated with elevated amyloid burden. Elevated pulsatility of arterial pressure, as a vascular factor indicative of vascular stiffness, is associated with AD. This study investigates whether increased magnitude of pulsatile stretch of human cerebral microvascular endothelial cells (hCMEC) alters expression and processing of APP. Design and method: hCMECs were cultured on flexible silicone chambers and subjected to 5%, 10% or 15% cyclic stretch (ShellPA stretch system, Menicon Life Science) for 18 hours at 1 Hz (n = 5–11 for each stretch magnitude). Comparison was made with controls (0% stretch) to evaluate the effect of pulsatility on APP. APP expression was quantified using western blots with glyceraldehyde 3-phosphate dehydrogenase as the loading control. APP processing was evaluated in the cell culture supernatants by ELISA for secreted Aβ42. Results were analyzed using one way ANOVA (mean ± SEM, % control) or Pearson correlation. Results: The densitometric analysis (expressed as a percentage of control values) of protein expression of APP showed that it was significantly higher at 10% of cyclic stretch (160.9 ± 21%) compared to both the static control (100%, p < 0.05) and 5% cyclic stretch magnitude (107.8 ± 12%, p < 0.05). The APP protein expression at 15% stretch magnitude (138.3 ± 12%) was slightly, but not significantly higher than the static control and 5% cyclic stretch. There was a significant correlation between the % stretch magnitude and secretion of A β42 (r 2 = 0.4132, p < 0.0001). Conclusions: Increasing cyclic stretch of cerebral vascular ECs altered the expression of APP and the secretion of A β42. Prolonged cyclic stretch may induce APP expression and A β formation. Findings mechanistically support the association of elevated haemodynamic pulsatility and arterial stiffness with AD.